2008
DOI: 10.1152/ajprenal.00506.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species participate in acute renal vasoconstrictor responses induced by ETAand ETBreceptors

Abstract: Just A, Whitten CL, Arendshorst WJ. Reactive oxygen species participate in acute renal vasoconstrictor responses induced by ETA and ETB receptors. Am J Physiol Renal Physiol 294: F719-F728, 2008. First published February 6, 2008 doi:10.1152/ajprenal.00506.2007.-Reactive oxygen species (ROS) play important roles in renal vasoconstrictor responses to acute and chronic stimulation by angiotensin II and norepinephrine, as well as in long-term effects of endothelin-1 (ET-1).Little is known about participation of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 73 publications
1
40
1
Order By: Relevance
“…In addition to eliciting vasodilation, NO blunts vasoconstriction produced by G protein-coupled agonists, such as ANG II, endothelin-1, and the catecholamines norepinephrine or phenylephrine (9,38,40). Exaggerated vasoconstriction by one of these agonists might explain the enhanced myogenic response during NOS inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to eliciting vasodilation, NO blunts vasoconstriction produced by G protein-coupled agonists, such as ANG II, endothelin-1, and the catecholamines norepinephrine or phenylephrine (9,38,40). Exaggerated vasoconstriction by one of these agonists might explain the enhanced myogenic response during NOS inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that O 2 Ϫ dismutation by tempol attenuates renal vasoconstriction induced by ANG II, AVP, endothelin, and norepinephrine, and that this vasoconstrictor action of O 2 Ϫ may involve quenching of NO and also an action independent of NO (39,40,65). On the other hand, our laboratory (65) has shown previously that O 2 Ϫ enhances the renal vasoconstrictor action of AVP primarily by limiting the bioavailability of NO, suggesting different roles as a function of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…These radicals increase the vascular tone, either through direct modulation of vasoconstrictive pathways or inactivation of NO, providing another possible mechanism of Hb-induced vasoactivity (43)(44)(45). Hb-derived free radicals can potentially activate platelets, and markers of platelet activation were indeed found to be increased in patients with sickle-cell disease (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…In A 1 ϩ/ϩ mice, elevated adenosine levels may enhance arteriolar contraction, but in A 1 -deficient mice this would only activate A 2 -receptors, and thus attenuate the contractile response to ANG II. Moreover, NO produced in the juxtaglomerular apparatus may attenuate the contractile responses via direct actions on vascular muscle cells (7,10) or indirectly via scavenging of ROS (25,30).…”
Section: Discussionmentioning
confidence: 99%